(untitled) (KULT_online, 2021)
How can we overcome the species-oriented mindset in teaching and learning? Can we design learning processes in which the welfare of animals is seen as the fundamental principle to begin with? While focusing on such questions in an interdisciplinary field, this anthology showcases creative and concrete guidelines to tackle the problem of species-oriented thinking.